Cancer-related fatigue and depression in breast cancer patients postchemotherapy: Different associations with optimism and stress appraisals. Issue 5 (October 2015) - Levkovich, Inbar; Cohen, Miri; Pollack, Shimon; Drumea, Karen; Fried, Georgeta
Abstract: Objective: Symptoms of depression and cancer-related fatigue (CRF) are common among breast cancer patients postchemotherapy and may seriously impair quality of life (QoL). This study aimed to assess the relationship between depression and CRF in breast cancer patients postchemotherapy and to examine their relationships to optimism and to threat and challenge appraisals. Method: Participants included 95 breast cancer patients (stages 1–3) 1 to 6 months after completion of chemotherapy. Patients submitted personal and medical details and completed the following: physical symptom questionnaires (EORTC QLQ–C30, and QLQ–BR23), a symptoms of depression questionnaire (CES–D), the Fatigue Symptom Inventory (FSI), the Life Orientation Test (LOT–R), and a stress appraisals questionnaire. Results: We found levels of depression, CRF, and appraisals of cancer as a threat to be moderate and levels of optimism and appraisals of cancer as a challenge to be high. Depression and CRF were positively associated. A multivariate regression analysis revealed that 51% of the CRF variance was explained and, together with physical symptoms and threat appraisal, were significantly associated with CRF. A total 67% of depression was explained and, and together with challenge and threat appraisals, were significantly associated with depression. Significance of Results: Although CRF and depression were often experienced simultaneously and both were found to be higher among individuals who gave higher appraisals of cancer as a threat, only depression was related to optimism and challenge appraisals, while CRF was related mainly to intensity of physical symptoms. The different pattern of associations between optimism and appraisals warrants further clinical attention as well as future study.